Basketball Free Throw Skill Level of Grade 8 Boys of Pius Gombong Junior High School - Wibowo, Tristianto Agung; Ndayisenga, Japhet; Susanto, Ratno (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Basketball is included in the junior high school sports curriculum. Shooting is a basic technique that basketball players must master. Youmust be able to make shots, because shooting can cover up the weaknesses of other basic techniques. To make an accurate shot must multiply practice by increasing confidence, mechanism, rhythm, and range. The purpose of this study was to determine the skill level of free throw basketball for grade 8 boys of Pius Gombong Junior High School. The research method used is the survey method. The results of the calculation study use a percentage descriptive formula. Data collection technique with free throw test from the calculation results, the results showed that overall, the basic technique of playing basketball for 8th grade boys of Pius Gombong Junior High School. The results of the research on the Shooting Ability Free throw of 8th grade male students of Pius Gombong Junior High School. Categorized either with a frequency of 58% or with a good predicate. Free throws in basketball games are needed to make points freely. Free throw itself is done without using obstacles so that it makes it easier for players to make points. The conclusion of the data analysis of the results of the study is known that the results of the analysis of shooting ability are free. Throw students.grade 8 boys of SMP Pius Gombong are categorized as good. Keywords: Skill level, Basketball, shooting, Free throw